2023
DOI: 10.3390/biology12111394
|View full text |Cite
|
Sign up to set email alerts
|

NF-kB Regulation and the Chaperone System Mediate Restorative Effects of the Probiotic Lactobacillus fermentum LF31 in the Small Intestine and Cerebellum of Mice with Ethanol-Induced Damage

Letizia Paladino,
Francesca Rappa,
Rosario Barone
et al.

Abstract: Probiotics are live microorganisms that yield health benefits when consumed, generally by improving or restoring the intestinal flora (microbiota) as part of the muco-microbiotic layer of the bowel. In this work, mice were fed with ethanol alone or in combination with the probiotic Lactobacillus fermentum (L. fermentum) for 12 weeks. The modulation of the NF-κB signaling pathway with the induction of Hsp60, Hsp90, and IkB-α by the probiotic occurred in the jejunum. L. fermentum inhibited IL-6 expression and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…More recently, we highlighted the benefits of L. fermentum in a mice model of oxidative stress damage and inflammation induced by chronic alcohol intake. The probiotic's protective and anti-inflammatory effects in the intestine, mediated by Hsp60 expression, seem to extend to the cerebellum, likely due to the maintenance of intestinal barrier integrity [65]. In this work, our in vitro data revealed that treatment with a probiotics mix can protect cells from H 2 O 2 -induced stress, reducing levels of the stress-inducible protein Hsp60, as shown by immunomorphological analysis of Hsp60 levels (Figure 3a).…”
Section: Discussionsupporting
confidence: 54%
“…More recently, we highlighted the benefits of L. fermentum in a mice model of oxidative stress damage and inflammation induced by chronic alcohol intake. The probiotic's protective and anti-inflammatory effects in the intestine, mediated by Hsp60 expression, seem to extend to the cerebellum, likely due to the maintenance of intestinal barrier integrity [65]. In this work, our in vitro data revealed that treatment with a probiotics mix can protect cells from H 2 O 2 -induced stress, reducing levels of the stress-inducible protein Hsp60, as shown by immunomorphological analysis of Hsp60 levels (Figure 3a).…”
Section: Discussionsupporting
confidence: 54%
“…The excessive expression of multiple cytokines in the inflamed intestine is the main factor of intestinal injury [36]. Probiotics also play a beneficial role in alleviating intestinal inflammation [37]. Cytokines are molecular messengers that can regulate and mediate immune responses, including pro-inflammatory factors and anti-inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%